2017
DOI: 10.1111/bjh.14987
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1 clinical trial evaluating marizomib, pomalidomide and low‐dose dexamethasone in relapsed and refractory multiple myeloma (NPI‐0052‐107): final study results

Abstract: SummaryMarizomib (MRZ) is an irreversible, pan-subunit proteasome inhibitor (PI) in clinical development for relapsed/refractory multiple myeloma (RRMM) and glioma. This study analysed MRZ, pomalidomide (POM) and low-dose dexamethasone (Lo-DEX) [PMD] in RRMM to evaluate safety and determine the maximum tolerated dose (MTD) and/or recommended Phase 2 dose (RP2D). Intravenous MRZ (0Á3-0Á5 mg/m 2 ) was administered over 2 h on days 1, 4, 8, 11; POM (3-4 mg) on days 1-21; and Lo-DEX (5 or 10 mg) on days 1, 2, 4, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 41 publications
0
35
0
1
Order By: Relevance
“…Phase III for MM Marizomib 371 A novel proteasome inhibitor that exhibits effects in patients with refractory and relapsed MM.…”
Section: Nanog Ubiquitinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Phase III for MM Marizomib 371 A novel proteasome inhibitor that exhibits effects in patients with refractory and relapsed MM.…”
Section: Nanog Ubiquitinationmentioning
confidence: 99%
“…370 Additionally, marizomib exhibits synergistic effects with bortezomib and lenalidomide or pomalidomide and low-dose dexamethasone in patients with refractory and relapsed MM. 362,371 In addition, marizomib has the ability to penetrate the blood-brain barrier and induce apoptosis in glioma cells with low toxicity on normal cells. 372 Thus, it has been applied in newly diagnosed glioblastoma (NCT03345095).…”
Section: Preclinical/researchmentioning
confidence: 99%
“…Marizomib was shown to selectively affect the cell viability of MM and Lymphocytic Leukaemia (CLL) cancer cells and have less toxicity on normal cells as compared to BTZ [215,217]. Marizomib was also effective in killing MM cells derived from patients with resistance to BTZ [124,215,218]. Clinical trials in patients with refractory or relapsed MM showed an overall response rate of 11% when marizomib was used as monotherapy [128], with the rate increasing to 53% when the drug was combined with pomalidomide and low-dose dexamethasone [218].…”
Section: Marizomibmentioning
confidence: 99%
“…Marizomib was also effective in killing MM cells derived from patients with resistance to BTZ [124,215,218]. Clinical trials in patients with refractory or relapsed MM showed an overall response rate of 11% when marizomib was used as monotherapy [128], with the rate increasing to 53% when the drug was combined with pomalidomide and low-dose dexamethasone [218]. Note worthily, marizomib treatment has been associated with some central neurotoxicity and has been shown to induce apoptosis glioma cells, these effects indicating that the drug penetrates the blood-brain barrier and that its use would be worth exploring as a potential treatment for brain cancer [124,219].…”
Section: Marizomibmentioning
confidence: 99%
“…Marizomib is currently being tested in multiple phase I, II, and III clinical trials for refractory multiple myeloma, leukemia, lymphoma, glioblastoma, and malignant glioma (NCT03345095, NCT02330562, NCT02103335, NCT02903069), both as a single agent and in combination therapies. The results from these clinical trials show that Mzb (both as a monotherapy and in combination therapy) is well-tolerated, and demonstrate its promising activity in multiple cancer types (51). Our pre-clinical data in this study generated using a range of in vitro and in vivo TNBC models provide a strong rationale to translate Mzb into a clinical trial in combination with standard-of-care chemotherapy for primary and metastatic TNBC patients.…”
Section: Molecular Analysis Of Primary 4t1br4 Tumors Revealed That Mzmentioning
confidence: 81%